LATAR SOSIAL MASYARAKAT INDONESIA DALAM NASKAH DRAMA CUMA SOAL CABE KARYA ILHAM ZOEBAZARY - Dian Roesmiati (Kantor Bahasa Kalimantan Timur, 2016)
This research aims to identity the social background of Indonesian society and author’s world viewpoint reflected in a drama script Cuma Soal Cabe. The research method used is qualitative research. The object of this study is the social background of society in CSC drama script. The approach applied here is sociology of literature which focuses on the theory of genetic structuralism. CSC drama script is a reflection of human fact which occurs in Indonesian society at the time that literary work exists. This research reveals Ilham Zoebazary’s world viewpoint in CSC drama script. The result indicates that CSC drama script is a development of the author’s world viewpoint which is a collective thought of his collective subject.